Kinetic of Drying of Banana Chip with Cabinet Dryer - Karyadi, Joko Nugroho Wahyu; Anggoro, Ascaryo Dwi; Bintoro, Nursigit (2013)
Drying banana chip are generally carried out by method of direct sun drying The research is conducted to evaluate drying process of banana chip with cabinet dryer. This research also aims to determine characteristics of drying banana chip and to analyze of air temperature to change the moisture content. Banana is blanched in hot water at temperature 80- 85oC in 10 minutes for easily peeled and then sliced in 2 mm and 6 mm thickness. The drying was done with variations of the fuel gas flow rate at 0,21 kg/h, 0,19 kg/h, and 0,17 kg/h and variations of thickness of slices of banana (2 and 6 mm of thickness). The decrease of moisture content is used to calculate the value of drying rate constant ( k), activation energy (Ea). High of gas flow high temperature drying is able to evaporate the water content to 4- 8% in 10 hours and 18- 24 hours if using biogas fuel, the materials placed on the bottom shelf, water content can decrease rapidly. Constant rate of drying for the relationship between decreased water content and time at a constant rate period LPG dryer range from 9,85- 15,26%/h. Activation energy at constant periods are about 452,73- 4.956,49 J/mol, while the falling rate periods ranged between 263,83- 2.159,96 J/mol. The drying efficiency value of LPG dryer range from 20,97 to 23,15%.